The significance of cephalopod beaks in marine ecology studies: Can we use beaks for DNA analyses and mercury contamination assessment?. Issue 1 (15th February 2016) - Xavier, José Carlos; Ferreira, Sónia; Tavares, Sílvia; Santos, Nuno; Mieiro, Cláudia Leopoldina; Trathan, Phil N.; Lourenço, Sílvia; Martinho, Filipe; Steinke, Dirk; Seco, José; Pereira, Eduarda; Pardal, Miguel; et al.
Abstract: Cephalopod beaks found in the diet of predators have been a major source of scientific information. In this study, we evaluated the usefulness of DNA and contaminants analysis (total mercury — T-Hg) in cephalopod beaks in order to assess their applicability as tools in marine ecology studies. We concluded that, when applying DNA techniques to cephalopod beaks from Antarctic squid species, when using flesh attached to those beaks, it was possible to obtain DNA and to successfully identify cephalopod species; DNA was not found on the beaks themselves. This study also showed that it is possible to obtain information on T-Hg concentrations in beaks: the T-Hg concentrations found in the beaks were 6 to 46 times lower than in the flesh of the same cephalopod species. More research on the relationships of mercury concentrations in cephalopod beaks (and other tissues), intra- and inter-specifically, are needed in the future. Highlights: Cephalopod beaks found in the diet of predators have been a major source of scientific information. We evaluated the usefulness of DNA and contaminants analysis (total mercury- T-Hg) in cephalopod beaks. We concluded that it does not allow obtaining DNA from beaks but it was possible using flesh attached to those beaks. The T-Hg concentrations were 6 to 46 times lower than in the flesh (beaks: from 0.004 to 0.047 mg kg − 1 dry weight) No clear relationships were found between T-Hg concentrations in beaks and body mass of the individuals studied. This study aims to stimulate more research on the relationships between mercury concentrations in beaks.